PERAN SISTEM INFORMASI DALAM MENDUKUNG PENGAMBILAN KEPUTUSAN MANAJEMEN PENDIDIKAN - Batlayeri, Hilarius (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2016)
Information is an important item for manegers of education when having to decide on enhancing educative organisation. The system of management information is a development of the science of management. The information system is a method by which manegers are able to come to decisions that can be accounted for. The management of information systems on activities is easier, inexpensive, effective and efficient when having to make a decision concerning management functions like: planning, organizing, actuating and controlling of which the result of the decision can be accounted for. The role of the information system facilitates manegers of education to make decisions in strategical, static and technical fields.